Design of an MR compatible fNIRS instrument - Emir, U; Ademoglu, A; Öztürk, C; Aydin, K; Demiralp, T; Kurt, A; Dincer, A; Akin, A (2005)
Acquiring functional near infrared spectroscopy (fNIRS) and functional magnetic resonance-imaging (fMRI) data are usually done asynchronously. In order to correlate these two different modalities' data, measurements must be performed at the same time. In this study, we have designed a new MR compatible continuous wave intensity based fNIRS device to overcome this problem. For MR compatible fNIRS, we used two LEDs with wavelengths at 660 and 870 nm. There are four photodiodes for light detection. LEDs operated in a sequential multiplexing mode with adjustable "on" time for each LED. Emitted and diffused light was transferred to and from the tissue through 10m long single mode plastic optical fibers (INDUSTRIAL FIBER OPTICS, INC.). By using fibers, we overcome MR compatibility problems that can be caused by semi-conductors on probe. This MR compatible fNIRS design can provide synchronous measurements with low cost.